Serum brain-derived neurotrophic factor levels mirror bone mineral density in amenorrheic and eumenorrheic athletes - Nose, S.; Yoshino, O.; Nomoto, K.; Harada, M.; Dohi, M.; Kawahara, T.; Osuga, Y.; Fujii, T.; Saito, S. (International Journal of Sports Medicine, 2019)
Amenorrhea and osteoporosis are strongly associated in female athletes. Amenorrheic women show lower serum levels of brain-derived neurotrophic factor (BDNF) than eumenorrheic women. BDNF is known to regulate bone tissue development and remodeling; thus, athletes with low serum BDNF levels may show low bone mass. This study investigated the associations between serum BDNF, estradiol, and bone mineral density (BMD) in female athletes. This study included 160 elite female athletes (21.7±4.3 years). Serum levels of BDNF and estradiol were in 195 blood samples obtained from 132 eumenorrheic athletes (EA) and 63 amenorrheic athletes (AA). BMD was measured in the radius, lumbar spine, pelvis, and legs using dual-energy X-ray absorptiometry. AA showed significantly lower serum BDNF levels than EA (p=0.017). Serum BDNF levels were positively and significantly associated with both serum estradiol levels (p=0.0004) and the BMD measured at all sites (all p<0.05). 10 AA received transdermal estrogen therapy, and serum BDNF levels were measured at baseline and 6 months after therapy. Hormone-treated AA demonstrated a significant increase in serum BDNF levels after 6 months (p=0.022). Thus, serum BDNF levels may be associated with decreased BMD and serve as an indicator of the therapeutic effect of estradiol supplementation in female athletes with osteoporosis.